(untitled) (Itinera, 2013)
The controversial picture of gay sexual promiscuity developed in Faggots, and the radical political positions portrayed in The Normal Heart during the AIDS epidemic have helped to build the reputation of Larry Kramer. However, in the same time, they seem to have made his discourse ineffective. Through the study of those two pieces, we are going to question the use of provocation in Larry Kramer’s work and its effects.